Anti-DNA autoantibody-producing hybridomas of normal human lymphoid cell origin. - Cairns, E (1984)
Fusion of human myeloma cell line GM 4672 and tonsillar lymphoid cells from a normal donor resulted in 13 primary hybridomas, which produced IgM anti-single-stranded DNA (ssDNA) antibodies, as determined in enzyme-linked immunosorbent assay. Nine of these primary hybridomas have been cloned and a total of 34 clones were obtained. Supernatants of these cloned hybridomas were tested for binding to ssDNA, native DNA, RNA, low molecular weight supernatant DNA, polydeoxyguanylate-polydeoxycitidylate, polydeoxyadenylate-thymidylate sodium salt, and cardiolipin. Supernatants from all clones but one showed polyspecificity when reacting with the antigens tested. That the clones were true hybridomas rather than transformed lymphoid cells was evidence by IgM anti-DNA antibody secretion, karyotype analysis, and HLA typing. These studies imply that immunoglobulin genes encoding for anti-DNA autoantibodies with a spectrum of nucleic acid specificities similar to systemic lupus erythematosus, exist among normal B lymphocytes.